Réponses

  • Utilisateur Brainly
2014-03-23T09:25:40+01:00
Voici un exemple :
f(x)=2x²-8x+3
     =2(x²-4x)+3
     =2(x²-4x+4-4)+3
     =2((x-2)²-4)+3
     =2(x-2)²-8+3
     =2(x-2)²-5
L’expression f (x) = 2(x − 1) + 3 est la forme canonique du polynôme f (x) = 2x − 4x + 5. En effet : 2(x − 1) + 3 = 2(x − 2x + 1) + 3
= 2x − 4x + 5 = P (x).
L’expression f (x) = 2(x − 1)² + 3 est la forme canonique du polynôme f (x) = 2x − 4x + 5. En effet : 2(x − 1)²+ 3 = 2(x² − 2x + 1) + 3
= 2x² − 4x + 5 = f (x).
Désolée j'avais oublié les ²